1965
DOI: 10.2136/sssaj1965.03615995002900050036x
|View full text |Cite
|
Sign up to set email alerts
|

Zonal Salinization of the Root System in Relation to Plant Growth

Abstract: Corn and tomatoes were grown in the greenhouses in boxes containing three horizontal soil zones with a layer of coarse quartz sand to separate the zones. Either fresh or saline waters were supplied to each soil zone through porous ceramic tubes to maintain a fairly uniform water suction in each zone. Intro duction of saline water into a given zone caused the uptake of water by the plant from that zone to decrease as soil salinity increased to a critical value, at which point water uptake ceased. The amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1969
1969
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 0 publications
2
16
0
1
Order By: Relevance
“…Growing tomato plants in nutrient solutions with an osmotic potential of -600 KPa for short periods decreased both the_ osmotic potential and the water content of their leaves. A reduction of the leaf osmotic potential in response to a drop of the external osmotic potential has also been observed in other studies (Cram, 1976;Lunin and Gallatin, 1965). Exposure to osmotic stress reduced the osmotic potential of the cell to -1400 KPa compared with -800 in the controls .…”
Section: Effects Of Salinitysupporting
confidence: 81%
“…Growing tomato plants in nutrient solutions with an osmotic potential of -600 KPa for short periods decreased both the_ osmotic potential and the water content of their leaves. A reduction of the leaf osmotic potential in response to a drop of the external osmotic potential has also been observed in other studies (Cram, 1976;Lunin and Gallatin, 1965). Exposure to osmotic stress reduced the osmotic potential of the cell to -1400 KPa compared with -800 in the controls .…”
Section: Effects Of Salinitysupporting
confidence: 81%
“…Investigators have reported that reduced plant water uptake from a zone of high salinity is by an increase in the uptake from a zone low in salinity (Lunin & Gallantin, 1965;Shalhevet & Bernstein, 1968). Although this takes place without significant reduction in yield, there is a general concern about how much salt can be stored in the root zone before leaching is needed (Hoffman, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…There are relatively few reported experinments oni water uptake by l)lant root systemiis growing under a nonuniform-i distribution of salt concentration (4,9,10). It is known that when saline conditions vary with depth, water extraction is niot uniform with depth (11).…”
mentioning
confidence: 99%